Ion‐Permeable Electrospun Scaffolds Enable Controlled In‐Vitro Electrostimulation Assay of Myoblasts - Serafina Pacilio; Francesco Decataldo; Roberta Costa; Tobias Cramer; Beatrice Fraboni; Giovanna Cenacchi; Maria Letizia Focarete (Advanced Materials Interfaces)
Abstract In‐vitro models are fundamental for studying muscular cell contractility and for wide‐screening of therapeutic candidates targeting skeletal muscle diseases, owing to their scalability, reproducibility, and circumvention of ethical concerns. However, in‐vitro assays permitting reliable electrical stimulation of cell contractile activity still require technological development. Here, a novel approach to electrically stimulate differentiated muscular cell contractility is reported exploiting the ionic conductivity and mechanical flexibility of 3D nanofibrous scaffolds. The electrospun poly(L‐lactide‐co‐caprolactone) scaffold allowed for C2C12 murine myoblasts horizontal elongation and myotubes formation. Scaffold porosity enables high ionic conductivity and strong electric field generation, orthogonally oriented to the scaffold surface. Electrically induced cell contractility is determined with atomic force microscopy (AFM) enabling real‐time monitoring of scaffold vibrations in liquid environment. Differentiated cell actuation is found to be linearly correlated to current amplitude and number of current stimuli. Integrating the 3D nanofibrous scaffolds with real‐time AFM monitoring provides highly accurate in‐vitro assays for biomedical research. The induction of electric fields orthogonal to the scaffold surface allows for accurately mimicking the excitation‐contraction coupling mechanism observed in native skeletal muscle tissue. This work paves the way for the quantitative study of muscular cell dynamic behavior and physiology, further evaluating therapy effectiveness for muscular pathologies.